Cardiovascular risk factors associated with frailty syndrome among hospitalized elderly people: a cross-sectional study - Tavares, Darlene Mara dos Santos; Colamego, Camila Gigante; Pegorari, Maycon Sousa; Ferreira, Pollyana Cristina dos Santos; Dias, Flávia Aparecida; Bolina, Alisson Fernandes (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Identification of frailty syndrome and its relationship with cardiovascular risk factors among hospitalized elderly people is important, since this may contribute towards broadening of knowledge regarding this association within tertiary-level services. This study aimed to evaluate the cardiovascular risk factors associated with frailty syndrome among hospitalized elderly people. DESIGN AND SETTING: Observational cross-sectional study in a public teaching hospital. METHODS: The participants were elderly patients admitted to clinical and surgical wards. The cardiovascular risk factors assessed were: body mass index (BMI), waist circumference, systemic arterial hypertension (SAH), blood glucose, total cholesterol, high-density lipoproteins (HDL), low-density lipoproteins (LDL) and triglycerides. To identify frailty syndrome, the method proposed by Fried was used. The data were analyzed through descriptive statistics, chi-square test (P < 0.10) and multinomial logistic regression (P < 0.05). RESULTS: A total of 205 individuals were evaluated. It was found that 26.3% (n = 54) of the elderly people were frail, 51.7% (n = 106) were pre-frail and 22% (n = 45) were non-frail. The preliminary bivariate analysis (P < 0.10) for the regression model showed that frailty was associated with BMI (P = 0.016), LDL cholesterol (P = 0.028) and triglycerides (P = 0.093). However, in the final multivariate model, only overweight remained associated with the pre-frail condition (odds ratio, OR = 0.44; 95% confidence interval, CI = 0.20-0.98; P = 0.045). CONCLUSION: States of frailty were highly present in the hospital environment. The pre-frail condition was inversely associated with overweight.